Use of site-blocking injunctions for the protection of trademark rights online - Žagare, Gunta (Riga Graduate School of Law, 2019)
The author analysed site-blocking injunctions and their legal basis at three levels, namely at the international, regional (the EU in particular), and the national (Latvia in particular) level. It was sought how the legal regulation on injunctions at the international level translates to the regional and national level, and how regulation at the regional level translates to the national level, and what peculiarities of the procedure are regulated at the national level. Importantly, the author analysed how that regulation applies to site-blocking injunctions in particular.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Trademarks; Latvia